Profile of Elderly Independence in Tluwuk Village, Wedarijaksa Pati - Widyaningsih, Heriyanti; Muniroh, Fitri Ambarwati; Fitriana, Vera; Arsy, Gardha Rias; Putri, Devi Setya; Faidah, Noor; Winarsih, Biyanti Dwi; Hartini, Sri; Pujiati, Eny (Poltekkes Kemenkes Aceh, 2024)
Background: Elderly is a stage when a person enters the age of 60 years and above where changes occur in various aspects such as biological, cognitive, psychosocial, spiritual, and economic functions, which can affect the level of individual independence. Independence is related to a person's ability not to depend on others and not require full direction in carrying out activities. Elderly independence refers to the ability to carry out daily activities independently, make their own decisions, and meet their needs without assistance. Aspects of elderly independence include the ability to care for themselves such as eating, dressing, using the toilet, moving, bathing and eating independently. This independence can certainly be the main capital for the elderly in maintaining their health. Purpose: To find out the level of independence of the elderly in Tluwuk Village, Wedarijaksa Pati . Methods: The type of research used is quantitative descriptive with a survey design. The sample used in this study was the entire elderly population at the Tluwuk village health post as many as 30 respondents with a total sampling technique. The inclusion criteria include elderly people aged ≥ 60 years who live in Tluwuk village, are able to communicate fluently and are willing to be respondents. The instrument used to assess the function of independence is the Barthel Index. Results: Based on the results of the analysis, there were 16 elderly people in the independent category (53.3%), 13 people in the mild dependency category (43.3%) and 1 person in the heavy dependency category (3.3%). Conclusion: Almost half of the elderly in Tluwuk village have a good level of independence and can carry out daily activities without depending on or needing help from other people.